Tarana : mulheres, migração e a economia do caju no sul de Moçambique, 1945-1975 - Penvenne, Jeanne (James Currey, 2019)
Between the late 1940s and independence in 1975, rural Mozambican women migrated to the capital, Lourenco Marques, to find employment in the cashew shelling industry. This book tells the labour and social history of what became Mozambique's most important late colonial era industry through the oral history and songs of three generations of the workforce. In the 1950s Jiva Jamal Tharani recruited a largely female labour force and inaugurated industrial cashew shelling in the Chamanculo neighbourhood. Seasonal cashew brews had long been an essential component of the region's household, gift and informal economies, but by the 1970s cashew exports comprised the largest share of the colony's foreign exchange earnings. This book demonstrates that Mozambique's cashew economy depended fundamentally on women's work and should be understood as "whole cloth."